Therapeutic potential of tyrosine-protein kinase MET in osteosarcoma - Zeng, Ming; Liu, Can; Gong, Haoli; Tang, Zhongwen; Wen, Jie; Wang, Sisi; Xiao, Sheng (Frontiers in Molecular Biosciences, 2024)
Osteosarcoma, the most prevalent primary bone tumor in children and young adults, can often be successfully treated with standard chemotherapy and surgery when diagnosed at an early stage. However, patients presenting with metastases face significant challenges in achieving a cure.Despite advancements in classical therapies over the past few decades, clinical outcomes for osteosarcoma have not substantially improved. Recently, there has been increased understanding of the biology of osteosarcoma, leading to the identification of new therapeutic targets. One such target is MET, a tyrosine kinase receptor for Hepatocyte Growth Factor (HGF) encoded by the MET gene. In vitro and in vivo studies have demonstrated that the HGF/MET pathway plays a crucial role in cancer growth, invasion, metastasis, and drug resistance across various cancers.Clinical trials targeting this pathway are already underway for lung cancer and hepatocellular carcinoma. Moreover, MET has also been implicated in promoting osteosarcoma progression. This review summarizes three decades' worth of research on MET's involvement in osteosarcoma and further explores its potential as a therapeutic target for patients with this disease.